2023
DOI: 10.3389/fimmu.2023.1247710
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationships between CD25 on immune cells and hip osteoarthritis

Hao Luo,
Yong Zhu,
Bin Guo
et al.

Abstract: ObjectivesPrevious research has indicated a potential association between immune factors and osteoarthritis (OA), but the causal relationship between CD25 expression on immune cells and hip OA remains enigmatic. To shed light on this relationship, this study utilized the two-sample Mendelian Randomization (MR) method.MethodsLeveraging genome-wide association studies (GWAS) data from the UK Biobank and arcOGEN, the investigation encompasses a substantial European cohort comprising 15,704 hip OA cases and 378,16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…With increasing research on T cell subsets, a group of cells capable of actively maintaining immune homeostasis and peripheral immune tolerance has been identi ed and de ned as Tregs (21). CD4 + CD25 + Tregs are negative immunoregulatory cells that play key roles in inhibiting the progression of autoimmune diseases, controlling potentially harmful in ammatory responses, and maintaining autoimmune homeostasis (22,23). Consequently, more CD25-expressing Tregs or higher CD25 expression levels can improve Treg function, which is essential for preventing the development of immunological in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing research on T cell subsets, a group of cells capable of actively maintaining immune homeostasis and peripheral immune tolerance has been identi ed and de ned as Tregs (21). CD4 + CD25 + Tregs are negative immunoregulatory cells that play key roles in inhibiting the progression of autoimmune diseases, controlling potentially harmful in ammatory responses, and maintaining autoimmune homeostasis (22,23). Consequently, more CD25-expressing Tregs or higher CD25 expression levels can improve Treg function, which is essential for preventing the development of immunological in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…In this view, the aggregation of neutrophils around the joints and the destruction of articular cartilage by neutrophil elastase (NE) are considered indispensable for the progression of OA [ 31 , 32 ]. A recent Mendelian randomization (MR) analysis also revealed a causal association between adaptive immune T cells and a reduced risk of hip OA [ 33 ]. Similarly, our study found that adaptively immunized lymphocytes and LMR were associated with a lower risk of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the diverse genetic backgrounds of populations, substantial variations in the frequency of genetic variants exist. This inherent diversity poses the risk of spurious associations between genetic variations and outcomes (11). To address this concern, we restricted the sources of GWAS data for both exposure and outcomes to the European population.…”
Section: Methodsmentioning
confidence: 99%
“…In the field of epidemiological research, traditional observational studies often introduce bias to research results owing to potential confounding factors and reverse causation, thereby compromising their reliability (11). Although randomized controlled trials (RCTs) can address the limitations present in observational studies, the considerable time, manpower, and financial resources required for them become a significant and unavoidable challenge (12).…”
Section: Introductionmentioning
confidence: 99%